Puerarin-pueraria starch-Span80 gel bead and preparation method thereof
By using Puerarin-puerarin starch-Span80 material to prepare gel beads, the problems of low gel strength and loose network structure of existing gel beads are solved, and the effects of high drug loading rate and good swelling characteristics are achieved, which are suitable for applications in the food and pharmaceutical fields.
Patent Information
- Application Number
- CN202411878673.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-14
AI Technical Summary
The gel strength of existing gel beads is low and the network structure is loose, so they cannot effectively achieve controlled drug release, which limits their application in the food and medicine fields.
Puerarin-puerarin starch-Span80 is used as the material for gel beads, and the gelatin starch is gelatinized in ultrapure water of sodium alginate by dispersing puerarin starch, the surfactant Span80 is added, and the puerarin-ethanol solution is added dropwise, and then it is dripped into calcium lactate solution to cure it into a ball, and the gel beads are obtained by vacuum freeze-drying.
The prepared gel beads have a porous three-dimensional network structure, which improves the adsorption and embedding ability of active substances. The texture characteristics are better than those of traditional gel beads, with good swelling characteristics and thermal stability, and have a high drug loading rate. They are suitable for use in different environments.
Smart Images

Figure CN119613806A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of preparation of plant-derived functional materials, and particularly relates to puerarin-pueraria starch-Span80 gel beads and a preparation method thereof. Background Art
[0002] In recent years, the gel bead system has become a research hotspot for scholars at home and abroad, and is widely used in the field of functional foods and medicine. Usually, proteins and polysaccharides are the two main raw materials for making beads. At present, the preparation of gel beads is mainly completed by utilizing the ionic cross-linking effect between polysaccharides and multivalent cations. Gel beads have very high requirements in food applications, and texture and sensory quality are also indispensable. Poor taste, color, taste or mouthfeel will limit their application in food. Gel beads as a carrier system for encapsulating active substances have the characteristics of high encapsulation rate, high safety, low cost, and good stability. Because the gel beads prepared with sodium alginate as the matrix have low gel strength and loose network structure, they cannot play a drug controlled release effect. Therefore, the development of a gel bead with good sustained release performance and strong functionality has become an urgent problem to be solved.
[0003] Pueraria root contains abundant puerarin and starch. As an isoflavone, puerarin has multiple biological activities, and has significant effects in vasodilation, neuroprotection, cardioprotection, anticancer, antioxidation, and anti-inflammation. However, its poor water solubility and low bioavailability limit its application in food and medicine. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a method for preparing puerarin-pueraria starch-Span80 gel beads.
[0005] The present invention also provides puerarin-pueraria starch-Span80 gel beads obtained by the preparation method.
[0006] The technical solution adopted by the present invention to achieve the above-mentioned purpose is: The present invention provides a method for preparing puerarin-pueraria starch-Span80 gel beads, comprising the following steps: (1) Weigh kudzu root starch, disperse it in ultrapure water containing sodium alginate, stir to fully gelatinize the starch, and cool to room temperature to obtain a gelatinized kudzu root starch solution; (2) Add a surfactant to the gelatinized kudzu starch solution, add the puerarin-ethanol solution dropwise after stirring, and continue stirring after the addition is complete; (3) The supernatant is absorbed and dropped into a calcium lactate solution to solidify into spheres, which are then freeze-dried in vacuum to obtain the product.
[0007] Furthermore, in step (1), the ratio of the kudzu root starch to ultrapure water is 1 g:50 mL; and the ultrapure water contains 1% sodium alginate.
[0008] Furthermore, in step (1), the stirring is magnetic stirring at 90° C. for 30 min.
[0009] Furthermore, in step (2), the amount of the surfactant added is 1.5% of the volume of the gelatinized kudzu starch solution; the surfactant is Span80; the ratio of the kudzu starch to the puerarin-ethanol solution is 1 g:2 mL; the concentration of the puerarin-ethanol solution is 0.5-10 mg / mL; and the stirring time is 30 min.
[0010] Furthermore, in step (3), the concentration of the calcium lactate solution is 0.1 mol / L; the solidification time is 30 min; and the dripping distance is 1.5-2.5 cm.
[0011] The present invention also provides puerarin-pueraria starch-Span80 gel beads prepared by the above preparation method.
[0012] The beneficial effects of the present invention are: (1) The surface of the gel beads prepared by the present invention after encapsulating puerarin has pores, and the structure is a porous three-dimensional network structure, which is conducive to the adsorption and embedding of subsequent active substances; the texture results show that in addition to elasticity, the hardness, cohesion, adhesiveness, chewiness and recovery of the gel beads before freeze-drying are: puerarin-pueraria starch-Span80 gel beads> puerarin-pueraria starch gel beads> pueraria starch gel beads; and it has good swelling properties, which can reach 6.94±6.34%; (2) The gel beads prepared by the present invention have good thermal stability and are basically stable in different pH, temperature and salt solutions. The drug loading rate is high. The embedding rate and drug loading rate of puerarin-pueraria starch-Span 80 gel beads are 62.38% and 9.22 µg / mg, respectively. The gel beads have potential biomedical application value in the human body. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 The following are photos of the appearance of three types of gel beads; A: Pueraria starch gel beads; B: Puerarin-Pueraria starch gel beads; C: Puerarin-Pueraria starch-Span 80 gel beads; Figure 2 SEM images of three types of gel beads; A: Pueraria starch gel beads; B: Puerarin-Pueraria starch gel beads; C: Puerarin-Pueraria starch-Span 80 gel beads; Figure 3Texture characteristics of three types of gel beads before and after freeze-drying; A: Pueraria starch gel beads; B: Puerarin-Pueraria starch gel beads; C: Puerarin-Pueraria starch-Span 80 gel beads Figure 4 Swelling ratios of the three gel beads; Figure 5 DSC graphs of three types of gel beads; Figure 6 XRD patterns of three types of gel beads; Figure 7 FTIR spectra of three types of gel beads; Figure 8 Swelling stability of three types of gel beads; A: pH; B: salt concentration; C: temperature. DETAILED DESCRIPTION
[0014] The technical solution of the present invention is further explained and illustrated by means of specific embodiments below.
[0015] Example 1 Puerarin-Pueraria Starch-Span80 Gel Beads Weigh 1g of kudzu starch and disperse it in 50mL of ultrapure water (containing 1% sodium alginate). Stir magnetically at 90℃ for 30min to fully gelatinize the starch. Cool to room temperature, add 1.5% Span-80 of the starch solution volume, stir for 30min, then drop 2mL of puerarin-ethanol (1mg / mL) solution drop by drop. Stir for 30min after the addition is complete. Draw 3mL of supernatant with a syringe and drop into 0.1mol / L calcium lactate. Solidify for 30min to form a sphere.
[0016] Comparative Example 1 Preparation of Pueraria Starch Gel Beads Weigh 1 g of Pueraria starch and disperse it in 50 mL of ultrapure water (containing 1% sodium alginate). Stir magnetically at 90°C for 30 min to fully gelatinize the starch. Cool to room temperature, draw 3 mL of supernatant with a syringe, drop it into 0.1 mol / L calcium lactate, and solidify it for 30 min to form a ball.
[0017] Comparative Example 2 Preparation of Puerarin-Pueraria Starch Gel Beads Weigh 1g of Pueraria starch and disperse it in 50mL of ultrapure water (containing 1% sodium alginate). Stir magnetically at 90℃ for 30min to fully gelatinize the starch. Cool to room temperature, then drop 2mL of puerarin-ethanol solution (1mg / mL) dropwise. Continue stirring for 30min after the addition is complete. Draw 3mL of supernatant with a syringe and drop into 0.1mol / L calcium lactate. Solidify for 30min to form a sphere.
[0018] Effect Example 1 1.1 Structural characterization of gel beads 1. Appearance and structure observation The appearance of the gel beads before freeze-drying was observed with the naked eye and photographed, and the morphology of the gel beads after freeze-drying was observed using a scanning electron microscope (SEM).
[0019] 2. Texture determination The hardness, elasticity, cohesion, adhesiveness, chewiness and resilience of the gel beads before and after freeze-drying were measured using a texture analyzer. A P 0.5 / R probe was used, and the conditions were set in the TPA measurement mode: pre-measurement speed 1mm / s, test speed 1mm / s, post-measurement speed 1mm / s, compression degree 50%, trigger force 10 g, and time 5 sec. Three gel beads with a complete and round appearance were selected from each batch of samples and placed in the center of the test bench. The gel beads were tested to obtain their indicators, and each test was repeated 6 times.
[0020] 3. Determination of Gel Bead Swelling Rate Weigh a certain mass of freeze-dried gel beads m, add them to 10 mL of ultrapure water, take out the gel beads every 20 minutes to absorb the surface water, and measure their mass m1. The total test time is 2 hours. The swelling rate calculation formula is as follows: 4. Determination of thermal properties of gel beads Weigh 2 mg of sample and 10 mg of deionized water in an aluminum crucible, seal it with a lid, and equilibrate it overnight at 4°C. Set another set of blank crucibles as controls. Set the nitrogen flow rate to 20 mL / min, the temperature range to 20-300°C, and the heating rate to 10°C / min.
[0021] 5. Gel Bead XRD Determination At room temperature, the diffraction angle (2θ) was scanned from 5 to 80° at a rate of 1 ° / min. The relative crystallinity (Rc) was calculated using the following formula (3): (3) Where: Ac is the crystal area; Aa is the amorphous area on the X-ray diffraction pattern.
[0022] 6. Gel Bead Infrared Spectroscopy The samples were prepared by potassium bromide tableting method and measured at room temperature with a scanning range of 4000~500 cm -1 , resolution 4cm -1 , using DTGS detector, air as blank, and scanning 64 times to get the average value of 2.3.6.4.7. 7. Determination of gel bead swelling stability The stability of the gel beads was determined by measuring the swelling rate and size changes of the three gel beads in different pH (2, 3, 4, 5, 6, 7, 8 and 9), temperature (30, 40, 50, 60, 70, 80 and 90 °C) and salt solution (50, 100, 150, 200, 250 mM and 300 mM). The gel beads were weighed (m), incubated at room temperature for 12 h to allow the gel beads to swell fully, then the gel beads were taken out and the excess water was absorbed with filter paper, and the swollen gel beads were weighed (m1), and the swelling rate was calculated.
[0023] 8. Determination of puerarin embedding rate in gel beads Take 10 mg of freeze-dried gel beads, add 10 mL of anhydrous ethanol, grind and crush, and ultrasonicate for 20 min. Use anhydrous ethanol as a blank and measure the absorbance of puerarin at a wavelength of 250 nm. The formula for calculating the embedding rate and drug loading of gel beads is as follows: 9. Gel Bead In Vitro Digestion Assay The preparation of simulated saliva (SSF) electrolytes is shown in Table 1. Take 30 mL of gel bead sample solution (5 mg / mL) in a centrifuge tube, add 27 mL of SSF electrolyte solution, 30 μL of 0.3 M CaCl2, and 1.5 mL of α-amylase (200 U / mL), and make up to 30 mL with ultrapure water. Samples are taken at 0, 1, and 2 min, respectively. After the oral stage, the digestive fluid is combined with SGF at a ratio of 1:1 (v / v), and 33.6 mL of SGF electrolyte solution, 4.2 mL of pepsin solution (2000 U / mL), 21 μL of 0.3 M CaCl2, and 1 M HCl (adjust pH to 2.0) are added. Make up to 40 mL with ultrapure water, incubate at 37°C for 2 h, and take 6 mL of sample solution at 0, 30, 60, 90, and 120 min, respectively. After centrifugation, the supernatant is taken and the absorbance of puerarin is measured at 250 nm.
[0024] The sample solution of simulated gastric juice digestion for 120 min was quickly cooled. After cooling, the same volume of gastric digestion solution was taken, and 28 mL of SIF electrolyte, 4 mL of pancreatic enzyme (100 U / mL), 4 mL of ox bile powder (10 mM), 160 μL of 0.3 M CaCl2, and 1 M NaOH (adjust pH to 7.0) were added to the centrifuge tube in proportion, and ultrapure water was added to 40 mL. The solution was incubated in a constant temperature shaker at 37 °C for 3 h, and 6 mL of sample solution was taken at 30, 60, 90, 120, and 180 min, respectively. After centrifugation, the supernatant was taken to determine the puerarin content.
[0025] The release rate of puerarin in the complex was calculated according to the following formula: Where: C represents the puerarin release rate (%); Lt represents the puerarin content in the supernatant at time t (μg / mL); L0 represents the puerarin content in the complex (μg / mL).
[0026] 2. Data processing All experimental data were expressed as mean ± SD and analyzed by one-way ANOVA using SPSS 26 software. P <0.05 was considered to be significantly different. P <0.01 indicates a very significant difference.
[0027] 3. Results and analysis 1. Photos of the appearance of gel beads The overall morphology of the three starch gel beads is as follows Figure 1 As shown. The size of the gel beads is usually related to the needle hole diameter of the syringe. In this experiment, a 1 mL sterile syringe was used for titration. The prepared gel beads were uniform in size, smooth in surface, and had a regular spherical shape with a diameter of about 0.4 mm. The average diameter of the three gel beads did not change significantly, indicating that the addition of puerarin and Span-80 had little effect on the diameter of the gel beads; there was no obvious difference in color between kudzu starch gel beads and puerarin-kudzu starch gel beads, both of which were transparent, while the gel beads prepared by adding Span-80 were white. In addition, attention should be paid to the titration height during the titration process to avoid tailing or tadpole-shaped gel beads. The titration height of kudzu starch and puerarin-kudzu starch gel beads was about 0.5~1 cm, and the titration height of puerarin-kudzu starch-Span 80 gel beads should be 1.5~2.5 cm to ensure its spherical structure.
[0028] SEM images of three starch gel beads at different magnifications Figure 2 As shown. Figure 2 -A shows that the kudzu starch gel beads are approximately spherical, but the surface is concave, which may be because the water in the gel beads sublimates more during the freeze-drying process, causing the gel beads to appear shriveled, concave, and wrinkled. Figure 2 -B and Figure 2 -C shows that starch granules and sodium alginate form approximately spherical starch gel beads through cross-linking. The surface of puerarin-pueraria starch gel beads and puerarin-pueraria starch-Span 80 gel beads are rough and have small pores, and the structure is a porous three-dimensional network structure, which is conducive to the adsorption and embedding of polyphenols by starch gel beads.
[0029] 2. Texture Analysis of Gel Beads The hardness, elasticity, cohesion, adhesion, chewiness and recovery of three kinds of gel beads, namely, puerarin-puerarin starch and puerarin-puerarin starch-Span80, before and after freeze-drying. Figure 3 As shown in Table 1. Compared with puerarin starch gel beads, the texture properties of puerarin-puerarin starch gel beads and puerarin-puerarin starch-Span80 gel beads before freeze-drying were improved except for the insignificant change in elasticity. The hardness increased from 113 g to 125 g, the cohesion increased from 0.28 to 0.39, the adhesiveness increased from 31 to 49, the chewiness increased from 21 to 32, and the recovery increased from 0.12 to 0.17, indicating that the gelation gradually increased after the addition of puerarin, and the gel network structure was more tightly bound. The hardness of the gel beads after freeze-drying was 653~741, and the adhesiveness was 111~156, which was much greater than the hardness of the gel beads before freeze-drying, while the elasticity, cohesion, chewiness and recovery were lower than those of the gel beads before freeze-drying, indicating that freeze-drying had a certain effect on the texture properties of the gel beads.
[0030] Table 1 Texture parameters of three types of gel beads before and after freeze-drying 3. Gel Bead Swelling Rate Analysis Figure 4 The following is a graph showing the changes in swelling rate of kudzu starch gel beads, puerarin-kudzu starch gel beads, and puerarin-kudzu starch-Span80 gel beads as a function of swelling time. As can be seen from the figure, the freeze-dried gel beads swelled to 15 to 30 times their original volume within 2 h, and the swelling rate was proportional to the swelling time. In the early stage of swelling, the gel beads rapidly absorbed water, allowing the water to fill the pores inside the gel beads through the interaction between polymer chains, thereby increasing the volume of the gel beads. Among them, the swelling rate of puerarin-kudzu starch gel beads was the largest, ranging from 14.77±2.97% to 36.94±6.34%, and the other two were relatively stable, thus forming an internal network structure with low water solubility and appropriate swelling rate.
[0031] 4. Analysis of thermal properties of gel beads Thermal properties of kudzu starch gel beads, puerarin-kudzu starch gel beads and puerarin-kudzu starch-Span 80 gel beads are shown in Figure 2 Figure 5and Table 2. The gelatinization onset temperatures of the three gel beads increased significantly, namely 155.32±11.19℃, 164.38±10.73℃ and 164.44±9.54℃, which may be because the starch is wrapped by calcium lactate film, which requires a higher temperature to gelatinize the semi-crystalline structure of starch. In addition, the peak temperatures of the three gel beads are similar, namely 163.76±7.07℃, 177.05±7.86℃ and 173.95±8.51℃, respectively, indicating that the three have the same thermal stability characteristics. Compared with the thermal enthalpy value of kudzu starch-gel beads (1728.9±39.74℃), the ΔH of puerarin-kudzu starch gel beads and puerarin-kudzu starch-Span 80 gel beads decreased to 557.4±222.17℃ and 1629.2±211.28℃, respectively. Table 2 Thermal characteristics of three gel beads 5. Gel Bead XRD Analysis The crystal structures of kudzu starch gel beads, puerarin-kudzu starch gel beads and puerarin-kudzu starch-Span80 gel beads were determined by XRD. Figure 6 As shown. The three gel beads have diffraction peaks at 2θ of 21.72°, 21.31° and 19.87°, respectively, which are typical b-type crystal structures. The intensity of the diffraction peak increases after adding puerarin, which indicates that no new crystals are formed in the gel bead complex, and puerarin starch and puerarin are simply physically mixed. At the same time, the characteristic peak of puerarin almost completely disappears, because puerarin is embedded in the starch cavity, and the crystal characteristics of puerarin disappear, indicating that puerarin is successfully embedded in the gel beads.
[0032] 6. Gel Bead Infrared Analysis Pueraria starch gel beads, puerarin-pueraria starch gel beads and puerarin-pueraria starch-Span80 gel beads were 4000-500 cm -1 FTIR in the wavenumber range such as Figure 7 The spectrum shows that the three types of gel beads have different -1 、3424 cm -1 and 3343 cm -1 The stretching vibration of hydroxyl groups is induced in the range of 1604 cm -1 、1599 cm -1 and 1616 cm -1 Stretching vibration shows a strong absorption peak at 1426 cm -1 、1427 cm -1 and 1427 cm -1The OH stretching vibration peaks corresponding to the puerarin-puerarin starch gel beads and the puerarin-puerarin starch-Span80 gel beads shifted, which may be due to the interaction between the hydroxyl group of puerarin and the glucose of starch. No new absorption peaks were generated in the entire spectral region, and the surface chemical structure of puerarin starch did not change significantly, indicating that no new chemical bonds were formed inside the gel beads.
[0033] 7. Analysis of swelling stability of rubber beads The thermal stability of the three gel beads was tested by swelling ratio at different pH, temperature and salt concentration. Figure 8 As shown. Figure 8 A shows that from acidic to alkaline environments, the three types of gel beads first increase and then decrease with the increase of pH value. The swelling rates of kudzu starch and puerarin-kudzu starch gel beads are the largest at pH = 6, which are 35.84±2.64% and 15.75±0.61%, respectively. The maximum swelling rate of puerarin-kudzu starch-Span80 gel beads is 16.08±0.58% at pH = 5, indicating that the gel beads have pH-sensitive decomposition characteristics, and the gel beads have potential biomedical application value in human blood (pH 7.4), stomach (pH 1.0-3.0), duodenum (pH 4.8-8.2) and other parts. Figure 8 B shows that the swelling rates of the three gel beads are relatively stable in different salt solutions, indicating that they are not greatly affected by ion concentration; Figure 8 C shows that at different temperatures, the swelling rates of puerarin-pueraria starch gel beads and puerarin-pueraria starch-Span80 gel beads do not change much, indicating that they are not sensitive to temperature. The swelling rate of pueraria starch gel beads is 29.57±1.47% at 70°C and then decreases, indicating that the gel beads are greatly affected by temperature.
[0034] 8. Puerarin embedding rate in gel beads The encapsulation efficiency of puerarin in puerarin-pueraria starch gel beads and puerarin-pueraria starch-Span 80 gel beads is shown in Table 3. The encapsulation efficiency of puerarin-pueraria starch gel beads is 49.23%, and the drug loading rate is 7.27 µg / mg; the encapsulation efficiency of puerarin-pueraria starch-Span 80 gel beads is 62.38%, and the puerarin content is 9.22 µg / mg. Compared with puerarin-pueraria starch gel beads, the addition of surfactant Span 80 can still improve the encapsulation efficiency and drug loading rate of gel beads for puerarin.
[0035] Table 3 Gel bead embedding efficiency and drug loading rate The present invention studies the gel properties of the complex by preparing gel beads, and uses SEM, texture, infrared spectrum, XRD, DSC, swelling rate, swelling stability, embedding rate and drug loading rate to characterize the structure of three types of gel beads. SEM and appearance pictures show that the gel beads are close to spherical, and there are pores on the surface of the gel beads after puerarin is embedded, and the structure is a porous three-dimensional network structure; the texture results show that in addition to elasticity, the hardness, cohesion, adhesion, chewiness and resilience of the gel beads before freeze-drying are: puerarin-pueraria starch-Span80 gel beads>puerarin-pueraria starch gel beads>pueraria starch gel beads, and the various texture indicators of the gel beads after freeze-drying are significantly greater than those of the gel beads before freeze-drying, indicating that freeze-drying affects the texture characteristics of the gel beads; the swelling rate results show that the gel beads have good swelling properties The swelling rate of puerarin-pueraria starch gel beads was the largest, reaching 6.94±6.34%; DSC results showed that the gel beads had good thermal stability; XRD and infrared spectroscopy results showed that the chemical structure of the complex did not change significantly, indicating that no new chemical bonds were formed inside the gel beads; swelling stability results showed that puerarin starch gel beads were greatly affected by pH and temperature, and the other two gel beads were basically stable in different pH, temperature and salt solutions; the embedding rate and drug loading rate of puerarin-pueraria starch gel beads were 49.23% and 7.27 µg / mg, respectively, and the embedding rate and drug loading rate of puerarin-pueraria starch-Span80 gel beads were 62.38% and 9.22 µg / mg, respectively.
Claims
1. A method for preparing puerarin-pueraria starch-Span80 gel beads, characterized in that: The following steps are involved: (1) Weigh kudzu root starch, disperse it in ultrapure water containing sodium alginate, stir to fully gelatinize the starch, and cool to room temperature to obtain a gelatinized kudzu root starch solution; (2) Add a surfactant to the gelatinized kudzu starch solution, add the puerarin-ethanol solution dropwise after stirring, and continue stirring after the addition is complete; (3) The supernatant is absorbed and dropped into a calcium lactate solution to solidify into spheres, which are then freeze-dried in vacuum to obtain the product.
2. The preparation method according to claim 1, characterized in that: In step (1), the ratio of kudzu root starch to ultrapure water is 1 g:50 mL; the ultrapure water contains 1% sodium alginate.
3. The preparation method according to claim 1 or 2, characterized in that: In step (1), the stirring is magnetic stirring at 90° C. for 30 min.
4. The preparation method according to claim 1, characterized in that: In step (2), the amount of the surfactant added is 1.5% of the volume of the gelatinized kudzu starch solution; the surfactant is Span80; the ratio of the kudzu starch to the puerarin-ethanol solution is 1 g:2 mL; the concentration of the puerarin-ethanol solution is 0.5-10 mg / mL; and the stirring time is 30 min.
5. The preparation method according to any one of claims 1 to 4, characterized in that: In step (3), the concentration of the calcium lactate solution is 0.1 mol / L; the solidification time is 30 min; and the dripping distance is 1.5-2.5 cm.
6. Puerarin-Kuarda starch-Span80 gel beads prepared by the preparation method according to any one of claims 1 to 5.